AB0299 The Five-Year Radiological Course and the Development of Functional Disorders in Patients with Early Rheumatoid Arthritis. (10th June 2014) - Ermakova, Y.A.; Karateev, D.E.; Luchikhina, E.L.; Demidova, N.V.; Smirnov, A.V.; Nasonov, E.L.
Abstract : Background: The functional status in rheumatoid arthritis (RA) has reversible and irreversible components. The irreversible component includes the structural changes in joints. The study of the radiological progression is especially important for a long time. Objectives: To investigate the radiological course of the disease and to study the influence of the joint destruction on the functional status in patients with early RA. Methods: We used the data of long-term Russian project "RADICAL" (Early Arthritis: Diagnostic, Clinical, Aggressive Treatment). A total of 193 patients with early RA (diagnosed for less than two year) according to American College of Rheumatology criteria included in the study from 2003 to 2007 (67, 5% RF (+); 57% ACCP (+), 86, 5% women, age of 49 [40-58]). Patients were followed prospectively for 5 years. They were treated DMARDs, including the biologic therapy - Infliximab, Rituximab, Adalimumab (24%), according the "tight-control" principle. The radiological investigation of hands and feet with the evolution of Sharp/van der Heijde Score (SHS), HAQ, DAS28 were performed every 12 months. Results: At the beginning of the observation 16% patients had joint erosions. The erosive arthritis has been verified at years 1-5 of follow-up in 27, 5%, 38, 5%, 49, 5%, 58%, 73% of cases, respectively. Baseline median [25th percentile, 75th percentile] of SHS was 0 [0-0]. From 1 to 5 years - 0 [0-10], 0 [0-4], 1 [0-8], 3 [0-12], 6 [0-14], respectively. Baseline median of HAQ was 1, 125 [0, 625-1, 75]. From 1 to 5 years the median HAQ changed to 0, 5 [0, 125-1, 0], 0, 5 [0-1, 0], 0, 5 [0-1, 0], 0, 5 [0-1, 0], 0, 75 [0, 125-1, 125], respectively. We found weak but significant correlation between SHS and HAQ. Baseline Pearson correlation coefficient was 0, 17, from 1 to 5 years – 0, 25, 0, 29, 0, 36, 0, 37, 0, 39, respectively. Conclusions: During the first 5 years of RA the erosive process in joints increased. However, the most of patients had only minimal or moderate radiological damage (SHS). The functional impairment was on minimal level during the total 5 years follow-up period. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4512